Makna Ketenangan Jiwa Dalam Tafsir Ayat Al-Nafs: Pendekatan Psikologi Islam Dan Tantangan Di Era Modern: The Meaning of Peace of the Soul in the Tafsir of the Al-Nafs Verse: The Approach of Islamic Psychology and the Challenges in the Modern Era - Fajar Hidayat; Abdul Adzim HS (Mozaic: Islamic Studies Journal, 2026)
The current phenomenon shows that many people have lost their peace of mind (ithmi'nān al-nafs) in the midst of economic pressure, identity crisis, and spiritual aridity. Many individuals seek to find peace through entertainment, relaxation, and meditation. However, these approaches are often temporary and do not touch the root of the problem: namely the spiritual dimension and the meaning of life; The purpose of the research is to explore the concept of peace of mind based on verses about nafs with a thematic interpretation approach (maudhui), as well as analyze it from the perspective of Islamic psychology to build an integrative and applicable understanding; This type of research is qualitative literature (library research) with a thematic interpretation approach (maudhui) and Islamic psychological analysis. Departing from the fact that the study of interpretation of al-Nafs is generally still normative and theological, it has not been deeply associated with the Islamic psychological approach and the context of modern life which is full of pressure, stress, and crisis of the meaning of life. This study seeks to integrate the understanding of thematic interpretation with the concept of contemporary Islamic psychology in a more relevant way to today's human reality. The concept of tazkiyatun nafs, muhasabah, dzikrullah which is the core of peace of the soul in Islam, is very relevant to be developed into a model of Islamic therapy, especially for Muslim people who long for a psychiatric approach that is in harmony with their faith values.